The Process of Meaning Formation in Adolescents: A Grounded Theory - Nasiri, Hamed; Faramarzi, Salar; Namdarpor, Fahimeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to explore the process of meaning formation in adolescents.Methods: The research method was qualitative and utilized a grounded theory approach. The research population consisted of adolescents aged 12–20 years in Isfahan, Iran. Sampling was conducted theoretically. Nine participants were included in the study, and data collection was carried out through semi-structured interviews. The data analysis process followed Glaser's (1987) methodology. At the end of the coding stages, the final model of the study was presented.Findings: The results revealed that meaning formation in adolescents occurs through five stages: the occurrence of conflict (a triggering event), expression of conflict (problematic coping with a painful and damaging context, emotional confusion, and protesting against meaning), confrontation with conflict (addressing unclear feelings, focusing on core pain (self-awareness), and developing acceptance capacity), processing conflict (recalling the experience, exploring, expanding and deepening, gaining insight into unmet needs, and processing and accepting one's and others' experiences), and the emergence of resolution and achieving integration (softening and adopting a new perspective, manifesting agency (decision-making), generating experience, and integrating with prior experiences).Conclusion: Based on the findings, it can be inferred that meaning formation in adolescents occurs as a process. Therefore, it can be concluded that the journey toward finding meaning is not a fixed or instantaneous event but a continuous and evolving process shaped by various experiences and reflections. This process unfolds as a series of interrelated stages, reflecting a dynamic and transformative approach to navigating and understanding significant life changes. This structured delineation of stages provides valuable insights into how individuals actively engage with and create meaning when encountering transformative moments.